Women's time: the lost variable of economic analysis - Lavado, Tamia (2017)
This article aims to draw attention to the working time of women and their contribution to the economy through the realization of unpaid domestic work. This domestic work is important for the maintenance of one of the factors of production such as work. Working together with capital are the two factors that allow the development of the economy. The analysis carried out contemplates the difference between women with and without children, the difference in the use of time according to the age range of women and the relationship between time available and perceived labor income using the data from the National Survey of Time Use (2010).